(untitled) (Khairulummah, 2024)
The removal of NAP (National Awami Party) government in Baluchistan in February 1973 marked a significant milestone in Pakistan’s political arena. It highlighted the strained relations between the central government and Baluchistan, particularly the conflict between Prime Minster Zulfiqar Ali Bhutto and the then NAP leadership. Key causes of the dismissal included, the London Plan allegation, the Coast Guard operation, tribal conflicts and the alleged discovery of Iraqi arms cache. The after math saw violent reactions from Baluch nationalists leading to the formation of Baluch people’s Liberation Front and heightened political tensions across Pakistan. The dismissal also strained Pakistan’s relations with Afghanistan. Overall, this event had far reaching consequences for Pakistan’s political stability and regional diplomacy.